Influence of Hospital Formularies on Outpatient Prescribing Practices: Analysis of the Introduction of a Local Formulary: A Single-Center, 2-Year Follow-Up, Retrospective Cohort Study of a Local Formulary in Japan - Norihito Kanai PhD; Masazumi Ando PhD; Momoko Shimodate B.S; Yoshiko Miyazaki PhD; Toshio Saito B.S (SAGE Publishing, 2022)
Purpose The impact of a hospital formulary was evaluated to provide a guide for the establishment of local formularies to optimize patient care and healthcare costs. Methods A formulary was introduced by formulary pharmacists of the Toda Medical Group for suggesting recommended medicines to physicians based on the medication history. Patients who were hospitalized in the rehabilitation ward of the Niiza Hospital and prescribed medicines according to the formulary introduced between April 2017 and March 2018 were included and followed-up for six months. Results Of the 183 patients screened, 154 patients were enrolled as the formulary's introduction patients (76 males/78 females, median age 78 years); 92% of these patients received formulary-proposed prescriptions at the specified timepoints; and 19 patients re-consulted at the Niiza Hospital after discharge and continued the same formulary medicines. The proposed acceptance rate by physicians was 100%. Most changes suggested introduced generic formulations. The doses were equivalent for all pharmacological classes with the exception of medicines that interfere with the renin-angiotensin system, which fell from 10.7 to 7.2 mg ( P < .0001). Overall daily medication costs fell at discharge compared to admission (38.5 vs. 94.6 yen per patient, respectively, P < .0001). This was valid for all pharmacological classes except for calcium channel blockers. Conclusion Hospital formulary-prescribed medications continued after discharge and promoted significant decreases in costs associated with outpatient prescriptions. Introducing a hospital formulary provides a basis for the introduction of local formularies and contributes to the reduction of local healthcare costs.